Workplace smoking policies and their association with male employees' smoking behaviours: a cross-sectional survey in one company in China - Gao, JiaNing (BMJ Group, 2010)
OBJECTIVES: The present work sought to evaluate different worksite smoking control policies and their associations with employees' smoking behaviours and attitudes among Chinese male workers. METHODS: This was a cross-sectional survey with a self-administered standardised questionnaire, conducted among seven production workplaces of one multinational company in Shanghai in 2008. In total, 1043 male workers were involved. Current smoking prevalence, daily cigarette consumption, quitting intention and their potential association with workplace smoking control policies (smoke free or restricted smoking) were measured. RESULTS: Current smoking prevalence in workplaces where smoke-free policies had been imposed for 3 years was 55.5%, about 18% lower than in workplaces that only restricted smoking. Smokers in smoke-free workplaces also smoked 3.4 cigarettes less per day, made more quit attempts, were more confident of successfully quitting and more willing to accept a company sponsored cessation programme. Those patterns declined or were not found among the workplaces where smoking control policies had been imposed for 10 years. Smoker quitting intentions were not associated with workplace smoking policies regardless of the duration of the policies imposed. CONCLUSIONS: A smoke-free workplace policy was found to have a significant association with lower smoking prevalence and daily cigarette consumption, but not with employee quitting intentions. Restrictive smoking policies had no impact on employee smoking behaviours. The impact of workplace smoking control policies may vary over time.